A Tribute to the Late Dr. Sulayman Shehu Nyang - Altaf Hussain (International Institute of Islamic Thought, 2019)
It was Fall 1998, here I was, at Howard University, the mecca. Walking the historic grounds of the campus, I was tracing the footsteps of luminaries and intellectual giants, scientists and activists, who gave birth to inventions and social movements, and who were of African, Afro-Caribbean and African American descent, among others. Before enrolling in the doctoral program in the School of Social Work, I had known of Dr. Nyang but only interacted with him in passing at a few programs. All over the world, for nearly four decades, among Muslims, Howard University was synonymous with Dr. Sulayman Shehu Nyang. This proud and brilliant son of Africa was known for his Gambian roots, his prolific scholarship, his contagious smile, his wit, his insights, his at once profound brilliance and his down to earth demeanor, and his steady hand as Chair of the African Studies department at Howard University. I can count with rare exception the number of times I introduced myself as being a doctoral student, an administrator, a faculty member and now a department chair at Howard University, and the almost instant reaction among Muslims – Oh yeah, Dr. Nyang is at Howard. I have never met anyone like him. That was my first reaction when I finally got to spend time with Dr. Nyang on the campus of Howard Univer- Altaf Husain serves as Associate Professor and Chair of the Community, Administration and Policy Practice Concentration at the School of Social Work, Howard University ...